(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article is devoted to the process of integration, which is increasingly gaining momentum in the modern world, transforming all spheres of social life. Media and integration influence each other. And, in turn, the media, being under the influence of this phenomenon, influence the Russian language and the speech culture of society. At the turn of the 20th and 21st centuries, the world found itself under the influence of a process called “integration”.